Pengaruh bahasa gaul terhadap bahasa Indonesia di kalangan mahasiswa Universitas Asahan - Dinda Tsurmaiza Fajhrin Sitorus; Karimaliana Karimaliana; Khairun Nisa (Jurnal Komunitas Bahasa, 2023)
The development of slang language among teenagers is increasingly prevalent due to the influence of technology. The environment also plays a role in shaping the use of slang language. Slang is used for various purposes, such as casual greetings, playful banter, teasing, reminding or reprimanding, and even to foster harmonious relationships in friendships, making communication more relaxed and less formal or monotonous for teenagers. This research aims to gain in-depth insights into the patterns of slang formation used by teenagers, the sources of slang language, the objectives behind its formation, as well as the factors that support the existence of slang language and its impact.Â This study employs a qualitative analysis approach, conducted by interviewing active students at Asahan University to understand the effects and influences resulting from the use of slang language among university students. The research indicates that the consequences and effects of slang language use can pose a threat to the presence of the Indonesian language and diminish its value, potentially even leading to the extinction of the Indonesian language. However, slang language also has positive effects, such as enhancing the creativity of teenagers in their language use.Â